Estimating Crop water Requirements of certain crops using modified Penman Method and Penman Montiath - FAO 98 in Benghazi plane region - Ikhneifir, Ali A.; Bobreeg, Hafez M.Y. (Al-Mukhtar Journal of Sciences, 2017)
Estimate of the crop water requirements depends mainly on, reference evapotranspiration (ETo) estimation, crop coefficient Kc, and type of irrigation system. Reference evapotranspiration represents the fundamental core of the estimation process of water requirements. Therefore one must pay attention to the selected method used in the calculation.This study is to compare the use of modified Penman method, which is theoretically sound and has gained acceptance as a standard method for estimating reference evapotranspiration, and FAO Penman-Monteith method which considered relatively accurate and consistent performance in both arid and humid climates. FAO Penman-Monteith method is recommended as the standard method for ETo prediction. Comparison of the estimated reference evapotranspiration by the two methods, modified Penman method gave higher estimates for ETo rage from 5.5 to 20.5%. But when comparing the results of crop water requirements in Benghazi plane region, the results got closer using the single crop coefficient technique for Penman- Monteith . Use of single crop coefficient technique based on long term metrological data, is suitable for planning and project design purposes. Use of dual crop coefficient, based on instantaneous data, is suitable for instantaneous irrigation scheduling frequent irrigations (not included in the scope of this study). Both methods gave very close results in the overall project water budgeting, crop water requirements and seasonal water storage requirements. This conclude that one may select either method, modified Penman or Penman-Monteith (single crop coefficient),to use for estimating crop water requirements for planning purpose. Both methods gave very close results for crop water requirements and project water demand estimates for Benghazi plane region project.